Uniform stable observer for the disturbance estimation in two renewable energy systems. (September 2015) - Rubio, José de Jesús; Ochoa, Genaro; Balcazar, Ricardo; Pacheco, Jaime
Abstract: In this study, an observer for the states and disturbance estimation in two renewable energy systems is introduced. The restrictions of the gains in the proposed observer are found to guarantee its stability and the convergence of its error; furthermore, these results are utilized to obtain a good estimation. The introduced technique is applied for the states and disturbance estimation in a wind turbine and an electric vehicle. The wind turbine has a rotatory tower to catch the incoming air to be transformed in electricity and the electric vehicle has generators connected with its wheels to catch the vehicle movement to be transformed in electricity. Abstract : Highlights: An observer is designed for the states and disturbance estimation of renewable energy systems. The gains of the proposed observer are found to guarantee its stability and the convergence of its error. The proposed method is used for the states and disturbance estimation in a wind turbine. The proposed method is used for the states and disturbance estimation in an electric vehicle.